Biomimetic Nanosponges Suppress In Vivo Lethality Induced by the Whole Secreted Proteins of Pathogenic Bacteria. Issue 6 (13th January 2019) - Chen, Yijie; Zhang, Yue; Chen, Mengchun; Zhuang, Jia; Fang, Ronnie H.; Gao, Weiwei; Zhang, Liangfang
Abstract: Polymeric nanoparticles coated with membrane of intact red blood cells have emerged as biomimetic toxin nanosponges (RBC‐NS) that absorb and neutralize bacterial virulence factors associated with numerous bacterial infections. Despite its promise, a clear correlation between in vitro neutralization of complex bacterial toxins and in vivo therapeutic efficacy remains elusive. In this study, the whole secreted proteins (wSP) of methicillin‐resistant Staphylococcus aureus (MRSA) are collected to induce lethality in mice. The wSP preserve the complexity of bacterial virulence profile while avoiding the intricacy and dynamics of infections by live bacteria. RBC‐NS are first quantified for their neutralization capacity against the hemolytic activity of MRSA wSP in vitro. Using a mouse model, in vivo studies further demonstrate that, by neutralizing the hemolytic activity, RBC‐NS confer significant survival benefits against wSP‐induced lethality. Furthermore, when mice are challenged with a sublethal dosage of MRSA supernatant, RBC‐NS reduce lung damages and inhibit the activation of nuclear factor kappa B in the spleen. These results provide a systematic evaluation of RBC‐NS toward the treatment of severe MRSA infections such as MRSA bacteremia and MRSA‐induced sepsis. Abstract : Toxin‐absorbing nanosponges are made by wrapping polymeric nanoparticles with red blood cell membranes. They can neutralize the hemolytic activity of the whole secreted proteins (wSP) from methicillin‐resistant Staphylococcus aureus, ameliorate wSP‐induced lethality in mice, and reduce organ damage. The observed therapeutic efficacy implies the potential of using these nanosponges for the treatment of severe bacterial infections.